A creative industrial design framework of the taxonomy for Chinese indigenous materials and relevant crafts - Jinjuan Duan; Mark Evans; Karl Hurn; Ian Storer; Zehwen Bai (2024)
Industrial designers have a need to acquire knowledge related to physical materials and undertake activities such as materials selection and materials-driven creative design. Chinese indigenous materials (CIMs) and relevant crafts are identified as a significant but currently untapped resource for designers. Existing research lacks systematic organization and classification for this rich resource making it difficult to develop an online materials database for creative design. To enable industrial designers to develop an understanding of CIMs, obtain design inspiration and stimulate creative design activity, this paper reports on the development of a framework for a taxonomy of CIMs. Through literature review and analysis of existing design tools, the purpose, ending conditions, basic methods and framework of a taxonomy were identified. Taking Xuan Paper as an example, a case study was undertaken to establish methods and processes. When combined with expert interviews and user questionnaires, the usefulness, efficiency and acceptability of the research framework were evaluated, optimized and validated. The findings indicate that a CIM taxonomy can support designers to systematically acquire materials and processing information, facilitate materials-driven creative design, material comparison/selection and provide a framework for the construction of CIM-related databases.